Conceptual Design of Modernized 270 VDC Electrical Power Distribution System for Hercules C-130 Aircraft - Ibrahim Hakyemez; Oguz Kagan Keles; Ozcan Kalenderli; Mustafa Bagriyanik; Kalenderli, Özcan; Bağrıyanık, Mustafa (Institute of Electrical and Electronics Engineers (IEEE), 2024)
There is a growing need for electrical power due to increased challenging electrical characteristics of newly developed avionics and mission system equipment in aircrafts. Therefore, with the development of More Electric Aircraft (MEA) and All Electric Aircraft (AEA) concepts, the problem of optimizing and modernizing the electrical power distribution system should be resolved with taking into consideration the weight constraint. In order to deal with this growing demand, power system architectures based on high voltage (270 VDC) and state-of-the-art power electronic devices are being applied to aircraft electrical power distribution systems. Accordingly, this paper evaluates the MEA concept and development in power electronics, conceptual design constraints of the power distribution system and lastly, contributions of 270 VDC distribution and state-of-the-art power electronics at the conversion level. The candidate MEA power distribution system is applied to the conceptual design of the Hercules C-130 Aircraft. The results illustrate that the proposed modernization approach has a positive impact on the total weight, volume, system reliability, electrical protection, and electrical power management system of the aircraft.
Keywords: electrical wiring interconnection system; AC/DC power converters; more electric aircraft (MEA); Electrical engineering. Electronics. Nuclear engineering; military aircraft; solid-state power controllers; electrical power system; TK1-9971